Democracy in Africa successes, failures, andthe struggle for political reform - Cheeseman, Nicholas (New York Cambridge University Press, 2015)
This book provides the first comprehensive overview of the history of democracy in Africa and explains why the continent's democratic experiments have so often failed, as well as how they could succeed. Nic Cheeseman grapples with some of the most important questions facing Africa and democracy today, including whether international actors should try and promote democracy abroad, how to design political systems that manage ethnic diversity, and why democratic governments often make bad policy decisions. Beginning in the colonial period with the introduction of multi-party elections and ending in 2013 with the collapse of democracy in Mali and South Sudan, the book describes the rise of authoritarian states in the 1970s; the attempts of trade unions and some religious groups to check the abuse of power in the 1980s; the remarkable return of multiparty politics in the 1990s; and finally, the tragic tendency for elections to exacerbate corruption and violence.
Includes bibliographical references and index.
Keywords: Democracy--Africa--History.